2009
DOI: 10.5465/amr.34.4.zok710
|View full text |Cite
|
Sign up to set email alerts
|

To Disclose or Not to Disclose? Status Distance and Self-Disclosure in Diverse Environments

Abstract: People who are demographically different from one another face a fundamental challenge in developing high-quality relationships in organizations. We build theory about how the status differences that often accompany demographic characteristics can hinder this development through their influence on disclosure of personal information. We theorize about the construct of status distance and how, ironically, disclosure of personal information may increase status distance instead of bringing individuals closer toget… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
106
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(107 citation statements)
references
References 158 publications
0
106
0
Order By: Relevance
“…These social and person identities are thought to develop over time but to be relatively stable across situations (Markus & Wurf, 1987;Phillips, Rothbard, & Dumas, 2009;Scott, Corman, & Cheney, 1998).…”
Section: Moderating Effects Of Employee Identitiesmentioning
confidence: 99%
“…These social and person identities are thought to develop over time but to be relatively stable across situations (Markus & Wurf, 1987;Phillips, Rothbard, & Dumas, 2009;Scott, Corman, & Cheney, 1998).…”
Section: Moderating Effects Of Employee Identitiesmentioning
confidence: 99%
“…Many studies have shown that acknowledging one's stigmatized social identity reduces interaction strains between individuals with and without stigmatized social identities, reduces perceptions of stereotypes associated with the social identities, and leads to more favorable evaluations of the individual who made the acknowledgment (Davis, 1961;Evans, 1976;Hastorf, Wildfogel, & Cassman, 1979;Hebl & Kleck, 2002). However, researchers have proposed (Phillips, Rothbard, & Dumas, 2009) and recent studies have found that stigma acknowledgment can be disadvantageous for those who make such acknowledgments as it results in negative evaluations (Hebl & Kleck, 2002;Tropp & Bianchi, 2007).…”
mentioning
confidence: 99%
“…Our study examines how disclosure of personal information about a newcomer affects team processes, team performance and perceptions of the newcomer. We suggest that sharing Personalizing Ethnically Distinct Team Members 5 personal information may help group members with similarities to develop trust, but it may not have the same effect in teams with demographically different members, where disclosures of personal information may only serve to highlight differences among team members and increase their discomfort (Phillips, Rothbard & Dumas, 2009). This is because the disclosure of personal information by individuals with distinct characteristics can accentuate differences and status distance (e.g., the degree of status difference between individuals; Blau, 1977), thereby undermining the formation of high-quality relationships.…”
Section: Introductionmentioning
confidence: 90%